1999
DOI: 10.1074/jbc.274.37.26485
|View full text |Cite
|
Sign up to set email alerts
|

SH2-B, a Membrane-associated Adapter, Is Phosphorylated on Multiple Serines/Threonines in Response to Nerve Growth Factor by Kinases within the MEK/ERK Cascade

Abstract: SH2-B has been shown to be required for nerve growth factor (NGF)-mediated neuronal differentiation and survival, associate with NGF receptor TrkA, and be tyrosylphosphorylated in response to NGF. In this work, we examined whether NGF stimulates phosphorylation of SH2-B on serines/threonines. NGF promotes a dramatic upward shift in mobility of SH2-B, resulting in multiple forms that cannot be attributed to tyrosyl phosphorylation. Treatment of SH2-B with protein phosphatase 2A, a serine/threonine phosphatase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 67 publications
2
47
0
Order By: Relevance
“…Alternatively, SH2-B␤ might take one or more of the proteins required for these events to the wrong subcellular location or affect the ability of FKHR to be phosphorylated on the casein kinase I phosphorylation sites Ser 322 and Ser 325 . Any of these scenarios could occur as a consequence of SH2-B␤(R555E) not binding to TrkA (or other neurotrophic receptor tyrosine kinases) and/or not being phosphorylated on tyrosines, serines, or threonines as a consequence of not binding to activated TrkA (57,75). However, the fact that overexpression of SH2-B␤ causes FKHR to shift to the cytoplasm in the absence of NGF suggests that modification of SH2-B␤ by TrkA is not necessary for SH2-B␤ to affect the subcellular distribution of FKHR.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, SH2-B␤ might take one or more of the proteins required for these events to the wrong subcellular location or affect the ability of FKHR to be phosphorylated on the casein kinase I phosphorylation sites Ser 322 and Ser 325 . Any of these scenarios could occur as a consequence of SH2-B␤(R555E) not binding to TrkA (or other neurotrophic receptor tyrosine kinases) and/or not being phosphorylated on tyrosines, serines, or threonines as a consequence of not binding to activated TrkA (57,75). However, the fact that overexpression of SH2-B␤ causes FKHR to shift to the cytoplasm in the absence of NGF suggests that modification of SH2-B␤ by TrkA is not necessary for SH2-B␤ to affect the subcellular distribution of FKHR.…”
Section: Discussionmentioning
confidence: 99%
“…In the PDGFR beta signaling pathway PSM appears not to control the PI3K or MAP kinase signaling cascades since cell-permeable PSM SH2 domain peptides which inhibit PSM-PDGFR beta association in vitro (Figure 1) and mitogenesis in vivo (Figure 4) did not aect PI3K or MAP kinase activity (data not shown). The signaling pathway employed in the mitogenic responses to PSM has not been identi®ed yet which will be a premier focus of future studies (Rui et al, 1999b).…”
Section: Discussionmentioning
confidence: 99%
“…An association of PSM/SH2-B was established with the insulin-like growth factor-I (IGF-I) receptor (IGF-IR) that depends on receptor activation and was mapped to phospho-tyrosine sites which are conserved between the insulin and IGF-I receptors (Wang and Riedel, 1998). For SH2-B beta an association was described with PDGFR in response to PDGF activation which stimulated SH2-B beta phosphorylation on tyrosine, serine, and threonine (Rui and Carter-Su, 1998) which was also reported in response to nerve growth factor by kinases within the MEK/ERK cascade (Rui et al, 1999b). In response to insulin, tyrosine phosphorylation had originally not been observed for any form of PSM (Rui et al, 1997;Wang and Riedel, 1998) but has more recently been reported including a role as a substrate of IR (Kotani et al, 1998;Ahmed et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the NLS, NES, and SH2 domain all are involved in the regulation of SH2B1 trafficking between the cytoplasmic and nuclear compartments. SH2B1 is also translocated to the plasma membrane [21] . A N-terminal polybasic region (S 145 KPKLKKRF), which overlaps the NLS, is required, but not sufficient, for SH2B1β translocation to the plasma membrane [22] .…”
Section: Metabolic Function Of Sh2b1mentioning
confidence: 99%